Experience of image-analysis of rye grain - P. Ä. Zykin; E. I. Utkina; A. V. Voylokov (Аграрная наука Евро-Северо-Востока)
The article presents the results of image analysis of size and color of rye grains of different color that is controlled by known genes. It was studied 23 samples of rye with the color of the grain visually described as yellow, green, brown and violet. Software GrainScan developed for wheat was adapted for computer analysis of digital images of rye kernels obtained with flatbed scanner. Software along with size allows calculating three-coordinates of color in three-dimensional color space CIEL*a*b*. Based on coordinate values a* and b* calculation of two additional parameters - C* and h* describing the saturation (purity) and tone (the color itself) of the grains, respectively, was made. It is shown that the individual analysis of size and color characteristics of the kernels give low values of standard errors. This allows revealing pairs of forms, which differ from each other for any of the studied parameters. The color of the rye grain cannot be described as the saturated color of one of the tones. In accordance to values of h*, it was possible to divide four visually selected groups into three ones. A composition of groups correspond to lack of anthocyanins in caryopsis (anthocyaninless, yellow-seeded, brown-seeded samples), the presence of anthocyanins in the aleurone layer (green-seeded samples) and the presence of anthocyanins in the pericarp (violet-seeded samples). The data obtained are discussed in connection with literature data on visual description of colors of rye grain, type of pigments, and the coloring of the individual layers of rye kernel.